Responsible Ferry, Happy Employees, and Quality Services: The Study of Fair Transport in the Ferry Industry: The Study of Fair Transport in the Ferry Industry - Sum, Carmen; Lau, Yui Yip; Dragomir , Cristina (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In the context of ferry industry, fair transport is a new concept and under-researched in the academic research and industrial practitioners. The ferry operators overlook responsible ferry, happy employees, and quality services are crucial to align with the United Nations Sustainable Development Goals. The role of fair transport is still ambiguous and unawareness of the society. Also, the government bodies, policymakers, and international organizations implement ineffective measures to support the idea of fair transport in a ferry industry. The paper mainly review the current ferry industry context for the new fair transport concept, and investigate the key roles of ferry operators and international organizations in the fair transport.